2020
DOI: 10.1074/jbc.ra120.015025
|View full text |Cite
|
Sign up to set email alerts
|

Iron-mediated degradation of ribosomes under oxidative stress is attenuated by manganese

Abstract: Protein biosynthesis is fundamental to cellular life and requires the efficient functioning of the translational machinery. At the center of this machinery is the ribosome, a ribonucleoprotein complex that depends heavily on Mg2+ for structure. Recent work has indicated that other metal cations can substitute for Mg2+, raising questions about the role different metals may play in the maintenance of the ribosome under oxidative stress conditions. Here, we assess ribosomal integrity following oxidative stress bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…While it has been shown before that exchange of Mg 2+ ions in the ribosome can have a detrimental effect on rRNA stability ( Winter et al, 1997 ; Polacek and Barta, 1998 ), research on the specific role of ribosome bound Fe 2+ for oxidative lesions generated through localized Fenton reactions is scarce in bacteria. Most of the work has been focused on eukaryotes and human neurodegenerative diseases specifically ( Ward et al, 2014 ; Dusek et al, 2015 ; Daglas and Adlard, 2018 ; Smethurst et al, 2020 ). However, since the core structures and functions of the ribosome are conserved ( Melnikov et al, 2012 ), it is not far-fetched to assume that similar findings can be expected for bacteria.…”
Section: The Transcribed Mrna Is Translated To Proteinsmentioning
confidence: 99%
“…While it has been shown before that exchange of Mg 2+ ions in the ribosome can have a detrimental effect on rRNA stability ( Winter et al, 1997 ; Polacek and Barta, 1998 ), research on the specific role of ribosome bound Fe 2+ for oxidative lesions generated through localized Fenton reactions is scarce in bacteria. Most of the work has been focused on eukaryotes and human neurodegenerative diseases specifically ( Ward et al, 2014 ; Dusek et al, 2015 ; Daglas and Adlard, 2018 ; Smethurst et al, 2020 ). However, since the core structures and functions of the ribosome are conserved ( Melnikov et al, 2012 ), it is not far-fetched to assume that similar findings can be expected for bacteria.…”
Section: The Transcribed Mrna Is Translated To Proteinsmentioning
confidence: 99%
“…Menadione is a pro-oxidant used as an extracellular stressor of yeast cells because of its stability in the medium during yeast culture treatment and high cell wall/membrane permeability (Jamieson 1992). In our experience, menadione has advantages over the commonly used hydrogen peroxide due to its stability in solution during storage, which improves data reproducibility among experiments (Shedlovskiy et al 2017b; Smethurst et al 2020; Zinskie et al 2018). Previous studies have found that treating yeast cultures with high doses of menadione (up to 600 μM) triggers excessive rRNA fragmentation (Mroczek and Kufel 2008; Shedlovskiy et al 2017b) followed by induction of the apoptotic program (Mroczek and Kufel 2008).…”
Section: Resultsmentioning
confidence: 98%
“…For example, the RSR-based approach allows modification of ribosomes with stressor like oxidants or chemotherapeutic drugs before supplying them into translation reactions. To illustrate RSR’s application in assessing activity of modified ribosomes, we tested two RNA modifiers: 1) the cell-permeable drug menadione (vitamin K3, or K3), which promotes oxidation of RNA and proteins in cells (Shedlovskiy et al 2017b; Smethurst et al 2020; Zinskie et al 2018); and 2) cell-impermeable drug cisplatin, also known to modify nucleic acids, including rRNAs (Dedduwa-Mudalige and Chow 2015; Melnikov et al 2016). Purifying translationally active ribosomes from cell cultures (for menadione treatment) or CFE (for cisplatin treatment) allowed us to analyze both drugs’ effects on ribosome-regulated translation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Mn 2+ ‐containing catalase, a very ancient member of the ferritin superfamily, detoxifies H 2 O 2 (Klotz & Loewen, 2003; Zamocky et al., 2008). Under H 2 O 2 stress, OxyR facilitates Mn 2+ replacement of Fe 2+ in ROS‐sensitive enzymes, preventing their inactivation by Fenton chemistry (Anjem et al., 2009; Smethurst et al., 2020; Sobota & Imlay, 2011).…”
Section: Discussionmentioning
confidence: 99%